Comparing Family, Friends and Satisfaction with School Experience as Predictors of Swb in Children Who Have and Have Not Made the Transition to Middle School in Different Countries - Bilbao-Ramirez, M (Elsevier Ltd, 2017)
Transition to middle school periods is especially vulnerable stages in which children need external support to facilitate their adaptation to middle education. In this regard, this study aims at observing how the social supports “family” and “friends” influence SWB before and after the transition to middle school. This is conducted taking into account the mediating effect of satisfaction with school experience in a stage where significant changes occur in the school setting. To this end, different countries that have in common a transition to middle school period taking place between 10 and 12 years old are selected. Two structural models were conducted, one for 10-year-old children and other for 12-year-old children. Both samples included 8923 participants from 4 countries (Chile, South Korea, USA and Algeria). The mean age of participants was 11.20 years (SD = 1.12). The overall analysis of the results from the two models indicates that support agents (family and friends) are significant to SBW before and after the transition to middle school period. In concrete, friend support is more important than family support to 10 and 12-year-old children. Nevertheless, satisfaction with school experience behaves as a mediator between friend support, family support and SWB, and has the greatest effect on SWB at both ages. Finally, differences observed in the invariance analysis across different countries are discussed. © 2017 Elsevier Ltd